DETERMINASI SOSIAL DAN GAYA HIDUP TERHADAP EPIDEMIOLOGI HIPERTENSI DI PROVINSI NTB: SEBUAH KAJIAN KESEHATAN MASYARAKAT - Darma Karno; Jaswadi, Jaswadi; Muh. Emilia Sa'id Rasyid; Lalu Iman Saptahadi; Baiq Reni Pratiwi; Yuly Peristiowati (Bajang Institute, 2025)
Objective: This article aims to analyze the social and lifestyle determinants that contribute to the epidemiology of hypertension in West Nusa Tenggara (NTB) Province. This study was conducted to understand how social, behavioral, and environmental factors influence the high incidence of hypertension, and how public health policies can be optimized for prevention and control. Methods: This study used a narrative literature review method by searching publications on Google Scholar, PubMed, ScienceDirect, and DOAJ, as well as official reports such as Riskesdas, the NTB Health Profile, and WHO reports. Keywords included